(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Within the context of the digital age, the development of a professional network plays a vital role in the career progression and advancement of students who seek to transition from academic environments to a professional setting. While the global platform offers a sense of widespread opportunity in the context of a networking forum, there remains a lack of academic nuance and personalized attention with regard to the student community. The goal of this project is to design and develop CAMPUS CONNECT, a professional networking site exclusively for the student community of the college. Through this platform, various features are to be provided, such that students can showcase their skills, share projects, internships, jobs, and form relationships with others within an academic environment that they trust and are comfortable with. To achieve this goal, the system was designed using user-centered design, which follows an agile methodology in its creation. The system also includes core components of a social networking site, such as user profiles, connections, sharing of projects, mentoring, and job sharing. The database for the system was designed with a structured form to handle user data, connections, and content efficiently while promoting a smooth flow of operations. Through the CAMPUS CONNECT implementation, the accessibility of networked opportunities, better collaboration between students, and the highlighting of student skills and accomplishments within the school community have been achieved. CAMPUS CONNECT has established a personalized and specific network system unlike other general network systems. In conclusion, CAMPUS CONNECT creates a nurturing digital environment that enhances community participation, sharing of knowledge, and increases the employability of students through closing the gap between learning and networking in a professional domain.